The Effectiveness of Walking Exercise on Hypertension - Padilah, Farhan Isma; Anguni, Ridha Wahdini; Putri, Suci Tuty; Rahmi, Upik (Scientific Journal of Nursing Research, 2025)
Hypertension is a major global health concern and a leading risk factor for cardiovascular diseases. Non-pharmacological approaches such as physical activity and lifestyle modification have gained attention as effective strategies to reduce high blood pressure. This literature review examines eight selected international studies that explore the effectiveness of walking-based and lifestyle interventions in managing hypertension. The findings consistently show that programs like brisk walking, culturally adapted walking interventions, and DASH diet combined with walking significantly reduce systolic and diastolic blood pressure. Some studies reported reductions of up to 20 mmHg systolic and 12 mmHg diastolic (p < 0.05). In certain cases, stretching exercises proved more effective than brisk walking for early-stage hypertensive individuals. These interventions also enhanced cardiovascular fitness (VO₂max), walking endurance, and self-efficacy in maintaining healthy habits. Overall, walking and lifestyle changes offer accessible, low-cost, and effective non-pharmacological options for controlling blood pressure. These approaches are recommended as part of a comprehensive hypertension management strategy.